Study of the Regulatory Role of N-Acyl Homoserine Lactones Mediated Quorum Sensing in the Biological Activity of Burkholderia gladioli pv. agaricicola Causing Soft Rot of Agaricus spp. - Elshafie, Hazem S.; Devescovi, Giulia; Venturi, Vittorio; Camele, Ippolito; Bufo, Sabino A. (Frontiers in Microbiology, 2019)
Many Burkholderia spp. produce in vitro secondary metabolites with relevant biological activities and potential practical applications. Burkholderia gladioli pv. agaricicola (Bga) possess promising biological activities regulated by N-Acyl homoserine lactones (N.AHLs) based quorum sensing (QS) mechanism. In the current study, N.AHLs-deficient (ICMP11096glad-I) and N.AHLs-complemented (ICMP11096glad-IR) mutants were constructed in which the gene coding for AHL synthase was inactivated by allelic exchange in glad I mutant strain. The aims of this research were to i) assess the antagonistic activity of the wild type (WT) and the glad-I mutant of Bga against Bacillus megaterium (G+ve) and Escherichia coli (G-ve), ii) screen their hydrolytic enzymes and haemolytic substances, iii) monitor the pathogenic effect against Agaricus bisporus and finally iv) analyze the bioactive secondary metabolites produced by WT and mutant strain using high performance liquid chromatography (HPLC). Results showed that N.AHLs-deficient mutant exhibited high reduction of antagonistic activity against the tested microorganisms and notable reduction of chitinolytic, proteolytic and glucanolytic activities and complete absence of haemolytic activity, and the glad-IR complemented mutant was able to regain the major part of these activities. Furthermore, N.AHLs-deficient mutant strain was unable to degrade flesh cubes pseudo-tissues of A. bisporus. On the other hand, the virulence effect of complemented mutant was like to the parental WT strain. HPLC analysis revealed that some of the single components produced by WT strain were absent in N.AHLs-deficient mutant and others were highly reduced. The out-findings of the current research gave a spot into the regulatory role of N.AHLs and QS phenomenon in the biological activity of Bga bacterium.